2013
DOI: 10.1158/0008-5472.sabcs13-p3-12-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P3-12-06: Statin use and outcome among breast cancer patients treated with neoadjuvant systemic chemotherapy

Abstract: BACKGROUND: Statins are cholesterol-reducing agents that affect intracellular pathways associated with tumorigenesis and inflammation. Preclinical studies have demonstrated that statins have anti-tumor effects and epidemiological studies have suggested that the use of HMG-CoA-reductase inhibitors is associated with improved long-term outcomes among breast cancer patients. In this study we sought to evaluate the effect of statins in the pathologic complete response (pCR) and survival outcomes among breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…After exclusion of 737 results based on review of the title and abstract, 80 results were selected for full text review. After a review of full texts, 14 studies which met our inclusion criteria were identified and selected for data extraction and meta‐analysis . A flow diagram depicting our literature search strategy and study selection process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After exclusion of 737 results based on review of the title and abstract, 80 results were selected for full text review. After a review of full texts, 14 studies which met our inclusion criteria were identified and selected for data extraction and meta‐analysis . A flow diagram depicting our literature search strategy and study selection process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Upon exclusion of three conference abstracts, statin use continued to be related to improved RFS (7 studies, HR 0.68; 95% CI 0.56–0.82) and a similar trend towards improved overall survival (6 studies, HR 0.71; 0.46–1.09) and cancer‐specific survival (6 studies, HR 0.70; 95% CI 0.46–1.06).…”
Section: Meta‐analysismentioning
confidence: 96%
See 3 more Smart Citations